2016
DOI: 10.1016/j.cryobiol.2016.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment of Addra gazelle (Nanger dama ruficollis) spermatozoa with cholesterol-loaded cyclodextrins improves cryosurvival

Abstract: Preserving genetic diversity of the critically endangered Addra gazelle (Nanger dama ruficollis) could be enhanced through the use of frozen-thawed sperm and artificial insemination. Our aim was to characterize Addra ejaculate traits and to assess the effects of cholesterol-loaded cyclodextrin (CLC) on sperm cryosurvival. Fresh ejaculates were treated with CLC (0, 0.5, 1.5, 3.0, and 6.0 mg/ml) prior to cryopreservation. All males produced spermic ejaculates with >75% sperm motility. The mean ± SEM seminal volu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 62 publications
2
1
0
Order By: Relevance
“…The significantly higher number of cells with progressive movement and rapid cells obtained with spermatozoa cryopreserved in the extender with 0.5 mg/120 × 10 6 sperm of CLC confirmed the more effective preservation of sperm cell function exerted by cholesterol insertion to cell membrane. The best concentration of cholesterol loaded cyclodextrins was 0.5 mg/120 × 10 6 sperm, and this result confirms similar findings in gazelle [ 35 ] and bull [ 36 ]. It has been reported that other low concentrations (0.75 mg/120 × 10 6 sperm, 1 mg/120 × 10 6 sperm and 1.5 mg/120 × 10 6 sperm) of CLC had a positive effect on motility parameters in ram [ 22 ] and bull [ 21 ].…”
Section: Discussionsupporting
confidence: 88%
“…The significantly higher number of cells with progressive movement and rapid cells obtained with spermatozoa cryopreserved in the extender with 0.5 mg/120 × 10 6 sperm of CLC confirmed the more effective preservation of sperm cell function exerted by cholesterol insertion to cell membrane. The best concentration of cholesterol loaded cyclodextrins was 0.5 mg/120 × 10 6 sperm, and this result confirms similar findings in gazelle [ 35 ] and bull [ 36 ]. It has been reported that other low concentrations (0.75 mg/120 × 10 6 sperm, 1 mg/120 × 10 6 sperm and 1.5 mg/120 × 10 6 sperm) of CLC had a positive effect on motility parameters in ram [ 22 ] and bull [ 21 ].…”
Section: Discussionsupporting
confidence: 88%
“…Extender with addition of 1 mg of CLC had no impact on the sperm features evaluated by CASA. The best concentration of cholesterol-loaded cyclodextrins was 0.5 mg, and this result confirms similar findings in stallions [19], gazelles [40] and bulls [41]. It has been reported that other concentrations such as 0.75 mg, 1 mg and 1.5 mg of CLC also had a positive effect on motility parameters in rams [14], stallions [42] and bulls [43].…”
Section: Discussionsupporting
confidence: 86%
“…Anesthesia was supplemented with ketamine hydrochloride (1.0 mg/kg; IV) and propofol (0.5 mg/kg; IV) to maintain an optimal anesthetic plane. Animal was subjected to a physical examination, testicular measurements, an ultrasound assessment of testes (5 MHz linear probe), and semen collection by electroejaculation [8]. Testicular ultrasound revealed well-demarcated, round, anechoic structures in the testicular parenchyma of both testes (Figures 1 and 2).…”
Section: Case Presentationmentioning
confidence: 99%